From a Deficit to a Surplus Country – The Case of Malta - Grech, Aaron (European Scientific Journal, ESJ, 2019)
Malta’s current account position has shifted dramatically in recent years, from one of the largest relative deficits in the euro area to one of the highest surpluses. Malta’s external accounts have improved since 2009 by about four times the change seen in the euro area. This article argues that cyclical demand factors did not cause this, while lower oil prices and a better real exchange rate played a minor part. Structural developments, such as improving energy intensity and falling import content, were more important drivers. The improvement in the current account reflects a recovery in the national saving rate, driven by better fiscal performance, and rising corporate and household savings due to higher activity among export-oriented services firms. Conversely investment has declined, as these firms rely more on human capital.